Effect of packaging with chitosan film containing Bunium persicum L. essential oil on chemical and microbial properties of chicken fillet - Abolfazl Kamkar; Ali Khanjari; Mahbubeh Oladi; Ebrahim Molaee Aghaee (Fasa University of Medical Sciences, 2017)
Background & Objective: Herbal essential oils like Bunium persicum L. due to having anti-microbial and anti-oxidant properties, can be effective in prolongation of food shelf life. Considering environmental consequences arising from plastic packs, biodegradable covering films such as chitosan combined with herbal essential oils are an appropriate approach to controlling the chemical and microbial factors of food. This study aimed at investigating the anti-microbial and anti-oxidant effect of Bunium persicum L. essential oil combined with chitosan film on chicken meat packaging. Materials & methods: Chitosan films were prepared with different percentage of Bunium persicum L. essential oil (0, 1 & 2%). Films were produced after homogenization and molding using casting method with glycerol (plasticizer) and tween 80 (emulsifier). Chemical and microbial tests were performed on days 0, 2, 4, 7 and 10 on chicken fillets without film (control) and those having different films, which were stored in°4 C. Statistical analysis was conducted using SPSS. Results: Chicken samples packed with various films indicated lower values of chemical and microbial factors compared with control samples (p≤0.05) and generally a dose-response trend was observed by addition of essential oil. Conclusion: Chicken meat packing with chitosan film, especially by adding different levels of Bunium persicum L. essential oil can play an inhibitory role in increasing effective factors related to chemical and microbial spoilage.